An innovative technology of directional propagation of hydraulic fracture guided by radial holes in fossil hydrogen energy development. (26th February 2019) - Liu, Xiaoqiang; Qu, Zhanqing; Guo, Tiankui; Tian, Qizhong; Lv, Wei; Xie, Zhishuang; Chu, Chunbo
Abstract: Conventional hydraulic fracturing fails to develop low permeability reservoirs of fossil hydrogen energy that are not located in the direction of maximum principal in-situ stress. A new technology of fracture propagation guided by radial holes is proposed, which can realize directional propagation of hydraulic fracture along radial holes in fossil hydrogen energy development. In order to verify this new technology, a model of radial holes combined with hydraulic fracturing is established by the ABAQUS extended finite element method. Simulation results show that radial holes play a guiding role in fractures propagation. The influence extent of seven factors on the directional propagation of hydraulic fracture is listed as follows (from strong to weak): azimuth of radial holes > horizontal in-situ stress difference of fossil hydrogen reservoir > injection rate of fracturing fluid > Young's modulus of rock > permeability of fossil hydrogen reservoir > Poisson ratio of rock > viscosity of fracturing fluid. True tri-axial experiment is carried out to verify the accuracy of numerical simulation, and the result is consistent with numerical model, which indicates that numerical simulation is reliable. Highlights: A three-dimension stress coupled seepage model of radial holes is established. Numerical model proves that radial holes play a guiding role in the directional propagation of hydraulic fractures. The influence of seven factors on directional propagation of hydraulic fracture guided by radial holes is analyzed. Tri-axial hydraulic fracturing experiment is carried out to verify the accuracy of numerical simulation results.